The Effect of Glutathione on Serum Malondialdehyde (MDA) Level in Retinopathy of Prematurity Rat Models - Puspita Kusuma Dewi; Maharani Cahyono; Riski Prihatningtias; Liana Ekowati; Arief Wildan (Faculty of Medicine, Diponegoro University, 2020)
Introduction Retinopathy of prematurity (ROP) is the leading cause of blindness in newborn babies worldwide. The benefit of anti-oxidant was investigated for ROP cases by assessing its effect on the oxidative stress of the tissues. Glutathione is a primary endogenous in human body and its supplementation has been discovered for its benefits towards some ocular diseases. This study aims to understand the effect of glutathione on oxidative stress marker, serum Malondialdehyde (MDA), in ROP rat models.Materials and methods This was an experimental study with post test only controlled group design. Sixteen Wistar rats that met our study criterias were divided into two groups, study group and control group. The study group were exposed to 95% oxygen for 4 hours / day followed by normoxic laboratory condition for 20 hours. Glutathione 1.5 mg / day were injected intramuscularly to rats in study group. The control group was exposed to 95% oxygen followed by normoxic laboratory condition with the same manner, and did not received glutathione. This cycle was repeated for 14 days. Both groups were settled in a room temperature settings on days 15-22. Serum sampel was collected from retroorbital vein. The malondialdehyde level was analyzed using MDA analyser kit.Results MDA level was found significantly higher in study group compared to control group (546.99 ng/ml vs 201.51 ng/ml, respectively, p 0,001).Conclusion Our study demonstrated a higher MDA levels in ROP rat models given glutathione injection compared to the control group.